EFEKTIVITAS METODE TALAQQI DALAM MENINGKATKAN HAFALAN AL-QUR’AN PESERTA DIDIK DI SDIT ULUL AL-BAB WELERI - Leni Dwi Haryani; Muhtar Arifin Sholeh (Universitas Islam Sultan Agung, 2019)
The talaqqi is a method that is very suitable for beginner children especially those who cannot read well according to their lafad and makhraj. The talaqqi method is applied to make it easier for children to memorize by depositing or playing the memorization that has just been memorized to an instructor teacher to know the increase in memorization of the al-Quran. This article discusses the effectiveness of the talaqqi method in improving the memorization of al-Quran at SDIT Ulul Al-bab Weleri. The result is the implementation of the talaqqi method and the improvement of students' memorization with the highest intensity, which is very good intensity. There is a positive influence between the talaqqi method on the increase in memorization of al-Quran of students There is a significant influence between the talaqqi method and the memorization of al-Quran of students in SDIT Ulul Al-bab Weleri.Keywords: Effectiveness, Talaqqi Method, Al-Qur'an memorization